PENINGKATAN HASIL BELAJAR PEMBELAJARAN MATEMATIKA BANGUN DATAR KELAS LL SD - Nesa Novita; Al-Amin (ADIBA : JOURNAL OF EDUCATION, 2026)
Classroom action research (CAR) generally aims to improve student learning outcomes in the second grade at SDN 01 Pandam Gadang. Specifically, it aims to: 1) describe student activities; 2) describe the teacher’s management of the learning process; and 3) determine student learning outcomes in mathematics lessons on the topic of two-dimensional shapes. This Classroom Action Research (PTK) aims to improve the mathematics learning outcomes of second-grade students at SD UPTD 01 Pandam Gadang on the topic of objects around us. The background of this study includes low student learning outcomes caused by a lack of variety in teaching methods and insufficient use of concrete learning media. This study employed a lecture method with a cyclical approach comprising planning, action, observation, and reflection. The research subjects were eleven second-grade students at UPTD 01 Pandam Gadang Elementary School. Data were collected through tests, observations, and documentation. The results indicated that the application of the lecture method combined with visual aids significantly improved students’ mathematics learning outcomes, thereby facilitating their understanding. The average learning achievement of students in the pre-cycle was approximately seventy-three (73) percent, and after the improvement in Cycle 1, it reached ninety-one (91) percent. Additionally, students’ learning activities and motivation also increased during the learning process. As teachers, we always pay attention to all their learning needs so that the material can be well-received and easily understood by the students. These findings reinforce that using the lecture-demonstration method and the visual method can improve the mathematics learning outcomes of second-grade elementary school students regarding plane figures.